Short-term outcomes in patients with center-involving diabetic macular edema after a single dose of intravitreal bevacizumab - Christopher A. Turski; Mitchell A. Jacobs; Michelle M. Abou-Jaoude; Nicholas H. Fowler; Ryan Harpole; Emily Altman; John B. Chadwell; Gabriel Kindl; Hayley R. James; Shivani V. Reddy; Ramiro S. Maldonado (International Journal of Retina and Vitreous, 2022)
Abstract Background A significant portion of diabetic macular edema (DME) is refractory to anti-vascular endothelial growth factor (anti-VEGF) agents. This study investigates morphological and functional outcomes to a single intravitreal bevacizumab (IVB) injection in patients with center-involving DME (ciDME) at 4–6 weeks and compares treatment responders and non-responders based on spectral domain optical coherence tomography (SD-OCT) features. Methods IRB approved observational, retrospective chart review of patients with ciDME, identified by ICD-10 code, who received IVB and underwent baseline and 4–6 weeks follow-up SD-OCT imaging between January 1, 2016 and January 19, 2021. Patients who had received previous treatment with anti-VEGF or intraocular steroids within 1 year were excluded. Variables included best-corrected visual acuity (BCVA), central subfield thickness (CST) and total macular volume (TMV). Eyes were classified as responders if CST reduction was greater than 10%. OCT scans were graded qualitatively by two masked graders using Imagivault software. Paired Student’s t-tests, Wilcoxon signed rank tests and Chi-Square tests were used for analysis. Results A total of 334 prospective subjects were identified, and after applying exclusion criteria 52 eyes from 46 patients (mean age 64.22 ± 8.12 years, 58.7% male) were included. Mean BCVA did not significantly change with treatment, 63.9 ETDRS letters (~ 20/50) at baseline and 65.9 ETDRS letters (~ 20/50) post-treatment (p = 0.07). Mean CST decreased from 466 ± 123 μm at baseline to 402 ± 86 μm post-treatment (p < 0.001). 22 (42.3%) of eyes were categorized as responders and 30 (57.7%) as non-responders. Average change in CST from baseline in responders was -164 μm (p < 0.001) and + 9 μm in non-responders (p = 0.47). Vitreomacular adhesion (VMA) was more prevalent in non-responders (28.7% vs. 4.8%, p = 0.03). In addition, cyst location in the inner nuclear layer (INL) was present more frequently in responders (95.5% vs. 73.3%, p = 0.037) as was subretinal fluid (45.5% vs. 13.3%, p = 0.01). Conclusion The short-term response to a single IVB was sub-optimal with structural but no functional improvements. Greater baseline CST, presence of INL cysts and subretinal fluid may represent factors indicative of a better treatment response.